The confidence to research as a factor of higher education development - G. V. Varganova (Библиосфера, 2017)
The article shows main specific features of the modern stage of library science development, which raise barriers in research activity. The confidence to research is viewed as one of the social trust aspects and is a key factor determining new educational programs designing and strengthening cooperation between library and information science schools and library practitioners. The confidence to library research offers new perspectives, when the educational programs of library-information schools could be implemented in the context of the social requirements growth to library profession. The confidence to science is based on theoretical-methodological knowledge of researchers, their cultural and professional competences